Analisis Keabsahan Penyaluran Harta Zakat dalam Bentuk al-Qardh al-Hasan: Studi atas Materi Ijtima’ Ulama Komisi Fatwa MUI 2021 - Bakhrul Huda (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2022)
This study aims to analysis the suitability of the evidence base used to form the provisions of the ability to distribute zakat property in al-Qardh al-Hasan by making the material ijtima 'scholars of the Fatwa Commission MUI 2021 as the object of research. The research methodology is descriptive qualitative with a literature study approach that uses content analysis in reviewing some existing data. The results of this study show that the basis of the arguments used in the MUI Ijtima' material regarding the permissibility of distributing zakat assets in al-Qardh is still general in nature and tends to be less relevant. Therefore, there are four suggestions that need to be conveyed, namely; 1) the hadiths on the distribution of zakat assets that are pertinent to the theme of the problem description should be displayed; 2) the fiqh rules should be corrected by reviewing the benefits of distributing zakat assets in the form of al-Qardh al-Hasan; 3 the qawl (opinion) of the ulama displayed should be justified; 4) the provisions on the distribution of zakat assets in the form of Qardh should be concretely completed.